"I felt as if I was becoming myself anew": Transformative Learning Through Action Research Projects Carried out by Beginner Teachers. (January 2022) - Gawlicz, Katarzyna
This article explores action research as a tool for promoting transformative learning of prospective teachers. Drawing on two B.A. or M.A. projects carried out at a university in Poland in which teacher-students used action research and the educational ethnography design to examine themselves as teachers and their practice, the article demonstrates the potential of such an approach for the transformation of students' meaning perspectives and, eventually, of their personal and professional identities. The transformation the teacher-students experienced entailed their emancipation from the teaching models imposed on them in their institutions and the development of their personal teaching theories. This was followed by their transition to deliberate action, increased sense of agency, and readiness to assume responsibility for wider social change, consequently bridging the theory-practice divide. The author argues that despite the challenges of action research in the university context, its transformative potential makes it a valuable component of teacher education.